Does prophylactic PER oral warm water intake reduce incidence of shivering / James Joseph - James, Joseph (2018)
Background: Shivering is a frequent complication following anaesthesia, with an incidence of between 40-60% and 36-55% following general and neuraxial anaesthesia respectively. Shivering following spinal anesthesia is associated with many adverse events. The pharmacological prevention for post spinal shivering is diverse and not standardized amongst anaesthetists and evidence based protocols has not been established. The objective of this study is to assess the impact of oral administration of warm water administered prophylactically on the incidence of shivering after spinal anesthesia for Caesarean section. Methods: Pregnant women at term, undergoing low-risk elective and grade 3 emergency lower segment Caesarean section under spinal anesthesia were recruited into the study. They were randomly assigned to either to receive oral warm water after the delivery of the fetus or to receive routine care (pharmacological treatment). They were observed for shivering and graded according to Crossley & Mahajan grading if shivering develops. Results: 152 patients were recruited in the study, 75 in intervention arm and 77 in control arm. The overall incidence of shivering was 48%. There was no significant difference in the incidence of shivering between the interventional and control arms (49% v. 46%, p=0.888). Of those developed shivering, the majority (48%) had grade 3 (moderate) shivering. Two out of the 75 in the interventional arm reported mild adverse events (nausea and vomiting), which resolved upon reassuring them. iv Conclusion: There was no significant difference in shivering among those who received oral warm water as a prophylaxis against shivering compared to the standard care (monitoring and pharmacological treatment if shivering develops).